Strategi Nafkah Rumahtangga Petani Tembakau di Lereng Gunung Sumbing : Studi Kasus di Desa Wonotirto dan Desa Campursari, Kecamatan Bulu, Kabupaten Temanggung - Widiyanto, W; Hadi Dharmawan, Arya; W, Nuraini (Departement of Communication and Community Development Sciences, Faculty of Human Ecology, 2010)
The standard morality held to support livelihood strategy that the tobacco peasant families build, occured in two different forms of economical ethic. Each of them is placed in totally in opposition to the other. These are ”social-collectivism” ethic and ”individual-material acquisition” ethic. Each individual economic ethic build specific livelihood strategy that fit into the existing situation as faced by the peasant family. There are five different types of capitals at the tobacco peasant families disposal, namely: natural capital, phsycal capital, financial capital, human capital, dan social capital. In majority the peasant families of the research areas build common strategies of livelihood, namely: vertical solidarity, horizontal solidarity, debt, patronase, production strategy, “srabutan”, accumulation, and manipulation of commodity. The institutional system built by peasants as the implementation of their livelihood, namely: sistem nitip, royongan, gabung hasil panen, maro. These strategies are basically using social capital as a main capital to form livelihood strategies. In case of difficulties (in time of crisis), the tobacco peasant families build somewhat different strategies, namely: temporary migration. All These strategies (in normal and in crisis situation) showed that peasant of this area very flexible mechanism to survive. But, the most sustainable way to survive that the peasant family build is the strategy of using collectivity ties as a instrumental way to support their livelihood.